Observer variability in histopathological reporting of non-small cell lung carcinoma on bronchial biopsy specimens. Issue 2 (February 1996) - Burnett, R A; Howatson, S R; Lang, S; Lee, F D; Lessells, A M; McLaren, K M; Nairn, E R; Ogston, S; Robertson, A J; Simpson, J G; Smith, G D; Tavadia, H B; et al.
Abstract : AIMS: To evaluate the ability of histopathologists to sub-classify non-small cell lung carcinomas on bronchial biopsy material using the current World Health Organisation (WHO) classification. METHODS: Twelve histopathologists each reviewed 100 randomly selected bronchial biopsy specimens which had originally been reported as showing non-small cell lung carcinoma. For each case, two sections were circulated, one stained by haematoxylin and eosin and the other by a standard method for mucin (alcian blue/periodic acid Schiff). The participants were allowed to indicate their degree of confidence in their classification of each case. A standard proforma was completed and the results were analysed using kappa statistics. RESULTS: Where the participants were confident in their classification, they were actually quite good at sub-classifying the non-small cell carcinoma sections (kappa = 0.71, standard error = 0.058). Overall, however, the results were only fair (kappa = 0.39, standard error = 0.034). CONCLUSIONS: The majority of non-small cell lung carcinomas can be correctly categorised on adequate bronchial biopsy material. Where a confident diagnosis was made, both squamous carcinoma (kappa = 0.73) and adenocarcinoma (kappa = 0.83) were well recognised.